All-optical ultrafast electron bunch compression - Lim, Jeremy Zhen Jie (2018)
Ultrafast electron imaging (UEI) is a class of imaging techniques which utilizes electron bunches instead of laser pulses to probe the nature of light and matter with picometer spatial resolution and attosecond temporal resolution, making it ideal for studying the most rapid and minute of phenomena.